Survei Kompetensi Pedagogik dan Kepuasan Kerja Terhadap Kinerja Guru (Studi Kasus Guru Alumni Prodi PAI IAIN SAS Bangka Belitung) - *, Rada (Jurnal Penelitian, 2022)
This study aims to determine the effect of pedagogic competence and job satisfaction both partially and simultaneously on the performance of Islamic Religious Education teachers who are alumni of IAIN SAS Bangka Belitung. Both civil servant and non-PNS status in Bangka Regency, Bangka Belitung Islands Province. This research uses a quantitative approach with a survey method. The population in this study were PAI religion teachers from the formal education level of SD/MI and SMP/MTs in Bangka Regency with a sample of 240 teachers. The data collection instrument was a questionnaire consisting of 104 items. This research instrument was tested on 30 teachers. Test the validity of the instrument used is the validity of the content with expert judgment techniques. The reliability of the instrument uses the Alpha Cronbach formula. The analysis prerequisite tests carried out were linearity, normality and heteroscedasticity tests. The heteroscedasticity test uses a graphical regression pattern, the graph shows that the points spread randomly and spread above and below zero (Y axis) so that heteroscedasticity does not occur. Data analysis used multiple regression analysis techniques.The results showed: 1) pedagogic content had a significant effect on teacher performance with a contribution of 5.28%, 2) job satisfaction had a significant effect on teacher performance with a contribution of 6.32%, 3) pedagogical competency and job satisfaction together had a significant effect on teacher performance with a contribution of 10.2%.